The genetics of Charcot–Marie–Tooth disease: current trends and future implications for diagnosis and management - Hoyle JC; Isfort MC; Roggenbuck J; Arnold WD (The Application of Clinical Genetics, 2015)
J Chad Hoyle,1 Michael C Isfort,1 Jennifer Roggenbuck,1,2 W David Arnold1,3,4 1Department of Neurology, Division of Neuromuscular Disorders, 2Department of Internal Medicine, Division of Human Genetics, 3Department of Physical Medicine and Rehabilitation, 4Department of Neuroscience, The Ohio State University Wexner Medical Center, Columbus, OH, USA Abstract: Charcot–Marie–Tooth (CMT) disease is the most common hereditary polyneuropathy and is classically associated with an insidious onset of distal predominant motor and sensory loss, muscle wasting, and pes cavus. Other forms of hereditary neuropathy, including sensory predominant or motor predominant forms, are sometimes included in the general classification of CMT, but for the purpose of this review, we will focus primarily on the forms associated with both sensory and motor deficits. CMT has a great deal of genetic heterogeneity, leading to diagnostic considerations that are still rapidly evolving for this disorder. Clinical features, inheritance pattern, gene mutation frequencies, and electrodiagnostic features all are helpful in formulating targeted testing algorithms in practical clinical settings, but these still have shortcomings. Next-generation sequencing (NGS), combined with multigene testing panels, is increasing the sensitivity and efficiency of genetic testing and is quickly overtaking targeted testing strategies. Currently, multigene panel testing and NGS can be considered first-line in many circumstances, although obtaining initial targeted testing for the PMP22 duplication in CMT patients with demyelinating conduction velocities is still a reasonable strategy. As technology improves and cost continues to fall, targeted testing will be completely replaced by multigene NGS panels that can detect the full spectrum of CMT mutations. Nevertheless, clinical acumen is still necessary given the variants of uncertain significance encountered with NGS. Despite the current limitations, the genetic diagnosis of CMT is critical for accurate prognostication, genetic counseling, and in the future, specific targeted therapies. Although whole exome and whole genome sequencing strategies have the power to further elucidate the genetics of CMT, continued technological advances are needed. Keywords: Charcot–Marie–Tooth disease, next-generation sequencing, neurogenetic testing, nerve conduction studies, neuropathy